Towards in vivo biosensors for low‐cost protein sensing. Issue 7 (1st March 2013) - Ramesh, A.; Ren, F.; Berger, P.R.; Casal, P.; Theiss, A.; Gupta, S.; Lee, S.C.
Abstract : In vivo biosensing requires stable transistor operation in high‐salt concentration bodily fluids while exhibiting impermeability to mobile alkali ions that would otherwise render the metal‐oxide‐semiconductor (MOS) threshold voltage to drift. Metal oxide semiconductor capacitor structures using Al2 O3 as the gate dielectric were soaked in a sterile physiological buffer solution (PBS) up to 24 hours and for thicknesses from 100 to 10 nm. The triangular voltage sweep technique characterised alkali ion penetration, and measured no detectable alkali ions for the Al2 O3 capacitors. By contrast, the dose of alkali ions in silicon dioxide MOS capacitors steadily increased with increasing soak times in the PBS solution.